(untitled) (Baghdad Science Journal, 2025)
In this study the rate of infection in acute and chronic Toxoplasma gondii parasite that causes toxoplasmosis was determined. This study was Included 120 blood samples that collected from pregnant women revisions to some clinics and laboratories in Baghdad civil as well as 10 blood samples from non-infected women as a control group. All blood samples were collected in the first three months of the pregnancy period for detection toxoplasmosis by using serological tests of test kit ( Toxo , IgG.,Toxo , IgM ). To detect antibodies specialized type of IgG &IgM in acute and the chronic infection by Electro Clia manner using a Roche Cobas e411. The results showed that the total infection rate was (55.83)%, the rate of infection in acute (17.5)% While the rate of chronic infection was (38.33)%. As the results of the study showed that rate of acute infection of toxoplasmosis in pregnant women was significant decrease occurs when the level of probability of < 0.05 in glucose sugar levels, and a decrease in the level of hemoglobin and red blood cells, platelets and the high number of white blood cells when compared with the control group .